2017
DOI: 10.1108/aam-06-2016-0007
|View full text |Cite
|
Sign up to set email alerts
|

Functions of intermediaries in arts-based cooperations

Abstract: Purpose Arts-based cooperations between business and the arts create innovative solutions for companies by introducing artistic practices. Cooperations of this nature are predominantly prepared and implemented by intermediaries who act as “matchmakers” and bridge the cultural clash. The paper aims to discuss these issues. Design/methodology/approach For the present study on the function of such intermediaries, qualitative data material from interviews and case studies on arts-based cooperations was collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
(68 reference statements)
0
4
0
1
Order By: Relevance
“…The finding suggests that cultural factors positively and significantly impact RSR. Cultural factors refer to the cultural values and norms that influence a retailer’s behavior (Sandberg, 2017). This finding implies that retailers prioritizing cultural values such as respect for diversity and inclusivity are likelier to engage in socially responsible practices.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The finding suggests that cultural factors positively and significantly impact RSR. Cultural factors refer to the cultural values and norms that influence a retailer’s behavior (Sandberg, 2017). This finding implies that retailers prioritizing cultural values such as respect for diversity and inclusivity are likelier to engage in socially responsible practices.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al (2017) explored that CSR activities significantly influenced reputation and customer loyalty. Sandberg (2017) postulated that retailers could reduce transaction costs and risks contingent on asymmetric information. Involving retailers produces cost advantages compared to direct contact between companies and artists.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Proses terkait penelitian, yang menganalisis hambatan (seperti perbedaan budaya, pendorong, elemen (misalnya, artis, pemilik merek atau perantara), dan kondisi (seperti sebagai hak cipta dan aspek hukum lainnya). Selain artis dan pemilik merek, pertimbangan harus diberikan keberadaan dan fungsi berbagai perantara, termasuk biro iklan, penasihat seni dan penyedia layanan khusus (Sandberg 2017).…”
Section: Gambar 1 Konsep Art-brand Collaborationunclassified
“…In addition to the artist and the brand owner, consideration should be given to the existence and functions of various intermediaries, including advertising agencies, art advisors and specialised service providers (Sandberg, 2017). An analysis of case studies of art-based co-operations (Baumgarth and Sandberg, 2016) showed that best practice was invariably based on a triad of artists, companies and intermediaries.…”
Section: The Future: Directions For Further Researchmentioning
confidence: 99%